Lifestyle risk factors and comorbidities of cancer patients in a country with limited resources - Nejra Mlačo; Armin Šljivo; Ahmed Mulać; Amina Kurtović-Kozarić; Anes Pašić; Semir Bešlija; Šejla Cerić; Timur Cerić (Medicinski glasnik, 2020)
Aim: To investigate quality of life and exposure to lifestyle risk factors of cancer patients in Bosnia and Herzegovina and a correlation of cancer type with lifestyle risk factors. Methods: This was a cross-sectional study conducted on 200 cancer patients from the Clinical Centre of the University of Sarajevo. The respondents completed an anonymous questionnaire consisting of seven sections: basic patient information, physical activity, dietary habits including alternative medicine, tobacco use, alcohol consumption, anxiety, and comorbidities. Results: A total of 150 (75%) patients were overweight with 113 (56%) of them being less physically active after the confirmed diagnosis. After the diagnosis, 79 (40%) patients ate less food, and 154 (77%) healthier; 130 (65%) reported consumption of alternative medicine and food supplements, 39 (30%) spent >1/4 of average monthly salary on these products. Majority never consumed alcohol, 135 (68%) and 101 (51%) patients reported history of tobacco use. Being obese was an independent predictor for colorectal carcinoma; being less obese was linked to a decreased risk of breast cancer diagnosis. Physical activity was linked to a decreased risk of lung cancer diagnosis. Many patients (122; 61%) reported having chronic comorbidities, mostly hypertension, while 44 (22%) patients were proven to be clinically anxious. Conclusion: Our data suggest lack of public awareness of the consequences of unhealthy lifestyles. Risk factors such as alcohol consumption and tobacco use differed from other European countries. Significance of lifestyle changes after the diagnosis for reducing mortality and cancer recurrence requires further research. Prevention programs and more data are needed.
Keywords: body weight; Bosnia and Herzegovina; diet; medical oncology; tobacco use